Mathematical mechanics from particle to muscle - Cooper, Ellis D. (World Scientific series on nonlinear science. Monographs and treatises, 2011)
This title offers all the details of the mathematical mechanics underlying modern modeling of skeletal muscle contraction. The aim is to provide an integrated vision of mathematics, physics, chemistry and biology for this one understanding.